(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
The largest contributor to waste generation in Indonesia comes from household organic waste, which has the potential to pollute the environment if not managed properly. Conventional biotechnology utilises the activity of natural microorganisms to process organic waste into useful products, making it a relatively simple and easy-to-implement alternative for household waste management. This article aims to review various methods of domestic organic waste treatment based on conventional biotechnology. The method used is a literature study of relevant research results and scientific publications. The results of the study show that composting, liquid organic fertiliser production, and eco-enzyme production are effective methods in reducing the volume of household organic waste. Microorganisms such as Lactobacillus sp. and decomposing fungi play an important role in converting organic waste into nutrients for plants and natural cleaning fluids. Based on these results, it can be concluded that the application of conventional biotechnology has the potential to support sustainable household organic waste management while reducing the impact of environmental pollution.